Heritability of Productivity Elements of Chickpeas and its Importance for Practical Breeding - Kuzmina , Svetlana; Kazydub, Nina; Panchenko, Vladimir (KnE Life Sciences, 2021)
This study examined the genetics of the variability in quantitative traits and showed the possibility of selecting hybrids with a new, more favorable combination of traits, which is of practical interest for breeding. The main goal of our research was to determine the coefficients of heritability by the mass of seeds and the number of beans per plant in hybrid combinations of chickpeas, which allowed establishing the potential of parental varieties in the transfer of valuable genes responsible for plant productivity to offspring and expanding the spectrum of plant genetic diversity. The experiments were conducted in the fields of the educational and experimental farm of the Omsk State Agrarian University in the southern forest-steppe of the Omsk region in 2016-2018. The research included 6 chickpea samples with a complex of valuable traits from the Federal Research Center of the All-Russian Institute of Plant Genetic Resources named after N.I. Vavilov (VIR, St. Petersburg) and 8 hybrid combinations obtained on their basis. It was found that the mass of seeds per plant was characterized by low heritability (H2 = 22.8%) and the number of beans per plant was high (H2 = 54.0%). The variability of the mass of seeds per plant was largely paratypical and was influenced by environmental conditions; the variability in the number of beans per plant was due to genetic factors and indicated a high genetic diversity in the studied splitting chickpea populations. Selection based on the number of beans per plant was highly effective even in early generations of the hybrids. Selection by the mass of seeds from the plant was ineffective; it should be carried out in later hybrid generations under favorable growing conditions. The selection of valuable genotypes was most successful in hybrid chickpea populations by seed weight per plant: C-35 x ILC-2394, C-80 x ILC-2394, C-27 x ILC-2394, and by the number of beans per plant: C-27 x ILC-2394, C-27 x ILC-2402 Keywords: chickpeas, heritability, selection, genetics, productivity